An 82-GHz 14.6-mW Output Power Silicon Impact Ionization Avalanche Transit Time Transmitter with Monolithically Integrated Coplanar Waveguide Patch Antenna - Zhang, Wogong; Kasper, Erich; Schulze, Jörg (IEEE Transactions on Microwave Theory and Techniques, 2019)
The design, fabrication, and characterization of a 4.08 mm2 monolithic 82-GHz silicon impact ionization avalanche transit time (IMPATT) transmitter are presented. The vertical IMPATT diode was grown by molecular beam epitaxy and followed by the typical circuit fabrication process. The oscillator design is experimentally well verified both by the Kurokawa condition from impedance matching and by Barkhausen's criteria from the reflection coefficient aspect, respectively. An 82.5-GHz coplanar waveguide (CPW) patch antenna with 50-Ω input impedance is monolithically integrated to an IMPATT oscillator with similar working frequency. Under the biasing condition of 25 mA (13.41 V), the H-plane radiation pattern of the monolithic IMPATT transmitter was characterized at 82.17 GHz in an E-band anechoic chamber. From link budget calculation, the equivalent isotropically radiated power of the transmitter chip achieved 18.43 dBm (69.66 mW). With the simulated directive gain (7.35 dBi) of CPW patch antenna and measured CPW interconnect loss (0.57 dB), the output power of transmitter achieved 11.65 dBm (14.62 mW) with dc-to-radio frequency efficiency of 4.36%.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Anechoic chamber; Barkhausen's criteria; coplanar waveguide (CPW) patch antenna; dc-to-radio frequency (RF) efficiency; equivalent isotropically radiated power (EIRP); H-plane; Kurokawa condition; link budget; millimeterwave (mm-wave); monolithic impact ionization avalanche transit time (IMPATT) transmitter; oscillator; radiation pattern